PENGARUH KONSERVATISME AKUNTANSI, DEBT TO TOTAL ASSETS RATIO, LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Kurniawan, Christy; Suryaningsih, Rosita (EQUITY, 2018)
The objective of th is research is to examine the effect of accounting conservatism, debt to total assets ratio, liquidity, profitability, and firm size both partially and simultaneously towards earnings quality.In this research, accounting conservatism was measured by CONACC, liqui dity was measured by current ratio, profitability was measured by return on assets, and firm size was measured by log total asset, while earnings quality was measured by earnings response coefficient. The objects of this study are manufacturing companies which were listed in Indonesia Stock Exchange for period 2013 until 2015. The sample are 39 companies determined based on purposive sampling. The data used in this study are secondary data such as financial statements and historical share prices. The testing method used in this research is multiple linear regression. The result off this study are (1) accounting conservatism has a positive significant effect towards earnings quality (2) debt to total assets ratio has a positive significant effect towards earnings quality (3) liquidity has no positive effects towards earnings quality (4) profitability has a positive significant effect towards earnings quality (5) firm sizehas no positive effects towards earnings quality (6) accounting conservatism, debt to total assets ratio, liquidity, profitability, and firm size simultaneously have a significant effect towards earnings quality.